Nose-to-Brain Targeting of Resveratrol Nanoformulations - Bavafa, Amir; Sahab-Negah, Sajad; Forouzanfar, Fatemeh (Current Vascular Pharmacology, 2025)
Resveratrol [RES] is a polyphenolic stilbene with therapeutic potential owing to its antioxidant, anti-inflammatory, neuroprotective, and cardioprotective properties. However, the very poor oral bioavailability, fast metabolism, and extremely low stability under physiological conditions pose a severe detriment to the clinical use of RES. This newly developed field of nanotechnology has led to the formulation of RES into nanoformulations with the goal of overcoming metabolic-pharmacokinetic limitations and enhancing the targeted transport of RES to the central nervous system [CNS]. Among the various routes of administration, the combination of nose-to-brain [N2B] delivery via the intranasal [IN] route has recently garnered attention as a straightforward, non-invasive route for transport to the blood-brain barrier [BBB] for greater effects and less harmful systemic side effects by transporting nano-encapsulated RES into the neural tissues. This review critically summarizes the mechanisms and benefits of the N2B route for the delivery of RES nanoformulations, collating in vivo data demonstrating increased CNS bioavailability and stability and, consequently, improved therapeutic efficacy in animal models of neurodegenerative diseases. Compared with the more 'traditional' routes of administration, IN administration of RES nanoformulations is less toxic, cost-effective, and efficient in crossing the BBB. Therefore, this route represents a promising approach to the management of CNS disorders. Further optimization of nanoformulation design and clinical protocols is required to translate these promising findings into therapeutic strategies aimed at neuroprotection and disease modification in human CNS pathologies.
Keywords: nanoparticles